2016
DOI: 10.24023/futurejournal/2175-5825/2016.v8i1.227
|View full text |Cite
|
Sign up to set email alerts
|

Uso de Design Thinking como Experiência de Prototipação de Ideias no Ensino Superior

Abstract: RESUMONeste artigo apresenta-se um caso de uso do Design Thinking em uma disciplina de curso de graduação. O Design Thinking, que visa proporcionar uma inovação na forma de pensar, é composto por um ciclo de etapas que compreendem inspiração, ideação e implementação. Atualmente o termo inovação tem-se mostrado em ascensão em conjunto com o grande número de startups e a intensa procura das empresas para adaptar-se às novas tecnologias e criar diferenciais competitivos no meio em que atuam. Como experimento, foi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
3
0
8
Order By: Relevance
“…A study by Shamsuddin and Rozee et al [25] indicated that students liked to learn through using design-thinking, and that helped them acquire the skills of communication, building up a vision, and problem-solving, in addition to enhancing self-confidence. That was confirmed in a study by Martins and G. Signori et al [16] and Li and Zhan [35] which aimed to design the curriculum of a -Creativity & Innovation‖ subject in an informational systems course for undergraduate students at a private Brazilian university in accordance with the design-thinking model. The findings confirmed the important role of the design-thinking-based teaching method in encouraging scientific research within projects conducted by groups of students.…”
Section: Previous Studiesmentioning
confidence: 62%
See 2 more Smart Citations
“…A study by Shamsuddin and Rozee et al [25] indicated that students liked to learn through using design-thinking, and that helped them acquire the skills of communication, building up a vision, and problem-solving, in addition to enhancing self-confidence. That was confirmed in a study by Martins and G. Signori et al [16] and Li and Zhan [35] which aimed to design the curriculum of a -Creativity & Innovation‖ subject in an informational systems course for undergraduate students at a private Brazilian university in accordance with the design-thinking model. The findings confirmed the important role of the design-thinking-based teaching method in encouraging scientific research within projects conducted by groups of students.…”
Section: Previous Studiesmentioning
confidence: 62%
“…Design thinking helps teachers to be more successful through the change they make while designing-and with the people they work with within the design-various lessons, activities, and programs [13,14]. Today, the teaching process faces many difficulties, but all these problems and challenges could be considered as a chance for both teachers and students to design new solutions to improve both school and university classes [15,16].…”
Section: B Why Do Teachers Need Design Thinking?mentioning
confidence: 99%
See 1 more Smart Citation
“…Os autores embasados no referencial teórico de suas pesquisas, concordam que o protótipo pode ser um mediador, ou mídia do conhecimento como proposto por Souza (2019), auxiliando na interação e comunicação das ideias com todas as pessoas envolvidas no projeto, diminuindo a margem de interpretações errôneas, inclusive o usuário (Pereira et al, 2017). O protótipo é uma ferramenta para tangibilizar e testar as ideias, diferente de compartilhar palavras, permite a aplicação de materiais rudimentares aos mais sofisticados, evitando erros e retrabalhos no projeto, antecipando o futuro e transformando concepções do designer em um processo interativo (Rocha, Rubio, Filho, 2013;Domingues et al, 2014;Pereira et al, 2014;Martins et al, 2016;Meyer, 2018;Pereira et al, 2017;Almeida e Nojima, 2019).…”
Section: Procedimentos Metodológicosunclassified
“…Os testes geram o feedback permitindo avaliar e selecionar o que levar adiante, por isso, a prototipagem deve estar presente em todas as oportunidades do ciclo de projeto. Corroborando com Brown (2010) em testar as ideias o quanto antes, utilizando os materiais mais simples e baratos que tenha disponível, e progressivamente aplicar-se a resolução mais aproximada e refinada da solução final (Brunnet, 2015;Martins et al, 2016;Scherer et al, 2017, Correia et al, 2019Ricaldoni & Rezende, 2020).…”
Section: Procedimentos Metodológicosunclassified